The Value of Character Education in The Ruwahan Tradition at Jajar District Surakarta City - Septi Rochana, Evi; Rakhmawati, Ani; Sulaksono, Djoko (International Proceedings of Nusantara Raya, 2024)
Character education is hoped can form student strong character. The value of character education can be instilled in students through various things, one of which is through the Ruwahan Tradition which occurs in the Jajar sub-district, Surakarta city. The Ruwahan tradition is a tradition resulting from a mixture of Islamic culture and Hindu-Buddhist culture which aims to pray for ancestors. This research aims to describe the value of character education contained in the Ruwahan Tradition in the Jajar sub-district, Surakarta city. The method used in the research is descriptive qualitative. The data source that the researchers used was a phenomenon that occurred during the implementation of the Ruwahan Tradition in the Jajar sub-district, Surakarta city. Data collection techniques use in-depth interviews and direct observation. Data analysis uses interactive analysis. The results of this research show character education values in the implementation of the Ruwahan Tradition in Jajar Village, Surakarta, including: religious, mutual cooperation, nationalist, and integrity.